Analysis of Basic Forehand Table Tennis Skills at El-Jiilany Club, Tuban Regency - Apriyanto, Rohmad; Cahyani, Olivia Dwi; Yulianto, Dwiki (Journal Coaching Education Sports, 2023)
The training process in developing high-performance athletes is still not optimal as only 3 out of 10 athletes have achieved success. The purpose of this research is to analyze 10 athletes' basic forehand strokes using selected instruments to identify the reasons behind their lack of success in performing the fundamental movements. The research design is descriptive, employing a theory-based approach to collect, analyze, and present the gathered data. This study is quantitative in nature, with a sample size of 10 athletes. A practical test instrument was used for the analysis. The results of the research show the analysis of basic forehand stroke skills, including the initial posture, execution, and final posture, among the athletes at El-Jilany Club in Tuban Regency in 2022. Overall, the analysis indicates that the athletes' basic forehand stroke skills are satisfactory. However, there are still some athletes who demonstrate low skill levels in execution and final posture. The novelty of this research lies in the use of a practical test instrument selected by the researcher to analyze the basic forehand stroke skills of high- performance athletes. Furthermore, the study provides insights into the analysis of basic forehand stroke skills among successful athletes in a specific club, serving as a reference for athlete development in the same or other clubs.